The Concept of State Financial Loss Recovery Reviewed from the Perspective of the Judex Factie Court's Considerations - Zaldi Nasrudin; Setiawan Noerdajasakti; Milda Istiqomah (State Islamic University of North Sumatra Indonesia, 2025)
Corruption causes measurable state financial losses, making restitution a critical component of Indonesia's criminal justice system. Although mechanisms such as restitution and asset forfeiture are regulated under the Corruption Eradication Law, their implementation faces significant obstacles, including limited technical provisions, difficulties in tracing the origin of assets, and reliance on court decisions with permanent legal force. This study employs a normative juridical method to examine the regulatory framework governing restitution and its effectiveness in recovering state assets. The findings reveal that the absence of clear standards for calculating and enforcing restitution hampers legal consistency and weakens the recovery process. The study concludes that a reformulation of restitution policy is essential to ensure legal certainty and to transform restitution into an effective tool for restoring real state losses.